1987
DOI: 10.1111/j.1439-0523.1987.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self and Polycross Progeny Testing in Birdsfoot Trefoil (Lotus corniculatus L.) for Forage and Seed Yield

Abstract: Self and cross fertility, forage and seed yield of parents, self (SI), and polycross (PX) progenies were measured m a selected and an unselected population of birdsfoot trefoil {Lotus comicuiatus L.). Self fertility was significantly less than cross fertility in both populations. In a field planting SI progenies had lower forage yield in 1979 and 1980 and seed yield (relative to the parents) was less in the selected population tban the unselected in 1979. All correlation coefficients between years and progenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…In polyploid species, like L . corniculatus, inbreeding depression for forage yield is remarkable and it causes the reduction of selfed progeny performance with respect to the polycross one and it may result in lower correlation between the parents and selfed progenies (Onokpise et al ., 1987) .…”
Section: Resultsmentioning
confidence: 99%
“…In polyploid species, like L . corniculatus, inbreeding depression for forage yield is remarkable and it causes the reduction of selfed progeny performance with respect to the polycross one and it may result in lower correlation between the parents and selfed progenies (Onokpise et al ., 1987) .…”
Section: Resultsmentioning
confidence: 99%
“…According to Onokpise et al. (), forage and seed yield in S 1 progeny were lower than in polycross progeny in the birdsfoot trefoil, indicating inbreeding depression for these traits (Onokpise et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…(), forage and seed yield in S 1 progeny were lower than in polycross progeny in the birdsfoot trefoil, indicating inbreeding depression for these traits (Onokpise et al. ). Berdahl and Ray () reported that the S 1 population had lower yields than the OP population in crested wheatgrass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations